Protective effect of propolis on the antioxidant enzymes activities, characteristics of epididymal spermatozoa and histopathological structure of testis from rats treated with cyclophosphamide - Kaya, Emre; Yilmaz, Seval; Altay, Zuelal; Kaya, Seyma Ozer; Colakoglu, Neriman; Sarman, Emine (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
The aim of this study was to evaluate the possible therapeutic effect of propolis on cyclophosphamide (CP)-induced testicular lipid peroxidation and on the associated changes in spermatological parameters in epididymal spermatozoa and histopathological structure of rat testis. Rats were randomly separated into 4 groups with 7 rats in each group. Groups were formed as; 1 st group: Control group (untreated rats), 2 nd group: Propolis-treated group, 3 rd group: CP-treated group, and 4 th group: CP+Propolis-treated group. Propolis was administered to the rats at dose of 200 mgkg bw -1 by gavage for 7 days (d). CP was administered to the rats at a single dose of 150 mgkg bw -1 intraperitoneally. Propolis administration was started 2 d before CP administration and continued for 7 d. Malondialdehyde (MDA) and reduced glutathione (GSH) levels, catalase (CAT), glutathione peroxidase (GSH-Px), glutathione S-transferase (GST), and superoxide dismutase (SOD) activities, spermatological parameters, the weight of the reproductive organs, and the histopathological structure were determined. Compared to the control group, MDA levels and SOD activities significantly increased; while CAT and GST activities decreased, it was not found changed in GSH levels and GSH-Px activities in CP group. In the CP-treated group, there was decreased in sperm motility in epididymal spermatozoa, sperm density in epididymal spermatozoa, and weight of testis, prostate, epididymis and vesicula seminalis; while there was increased in abnormal sperm ratio compared to the control group in epididymal spermatozoa. Propolis normalized biochemical and spermatological parameters in epididymal spermatozoa. The histopathological examination of testicular tissue showed that the most significant histopathological change such as cell debris, invagination and degeneration occurred in CP group. In the pathogenesis of CP-induced testicular toxicity may play role the deterioration in oxidant-antioxidant balance and propolis may reduce severe side effects of CP-induced alterations.
Efecto protector del propóleo sobre las actividades de las enzimas antioxidantes, las características de los espermatozoides epididimarios y la estructura histopatológica de los testículos de ratas tratadas con ciclofosfamida
Keywords: Antioxidant; cyclophosphamide; malondialdehyde; oxidative stress; propolis